Linguistica Missionária: Summer Institute of Linguistics - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1993)
The paper discusses the history of the alliance between the evangelical mission Summer Institute of Linguistics and Latin American intellectuals between the 1930s and the 1970s. The purpose is to reconstruct the political and intellectual context in which this alliance took place in Mexico, Peru and Brazil. In particular, the role of the Inter-American Indian Institute as a space for mission contact with Latin American governments will be focused.
Missionary Linguistics: Summer Institute of Linguistics
Keywords: Educacao Bilingue; Educacao Indigena; Entrevista Linguistica; Historia da Linguistica; Missionarios; Summer Institute of Linguistics; CNPQ::LINGUISTICA, LETRAS E ARTES